Immigration and Racial Identity in Chimamanda Ngozi Adichie’s Americanah - Miss. Hanane BENTAYEB, Miss. Meriem LADJAL (My University, 2018)
Meriem ABSTRACT This dissertation proffers an inside insight into the description of issues such as race, immigration , loss , loneliness , identity and the position of the African in America in Chimamanda Ngozi Adichie's novel Americanah (2013). It evokes important questions on the nature of racism in the United States of America during the twenty first century. It gives a truthful description of the long history of racial inequality that faces immigrants in host land, the attitudes of whites toward issues such as skin color, hair texture, identity and how these issues still matter in term of beauty and success. The novel selected is thus studied both thematically and stylistically. Literature cannot be detached from historical background; that is why, the first chapter highlights the socio-historical issues and realities that surround and affect the writing of the novel, it draws attention to the theoretical background information relevant to the analysis of the selected novel in order to provide a basis. In the second chapter, we examine ways in which Adichie's novel Americanah can help broaden understanding of racism and immigration in the United States. The main objective here is to show that the different racial problems still exist in America because many people still believe the election of the black president erased four hundred years of slavery.
Keywords: Key words: immigration, racism, skin color, hair texture, identity, inferiority complex.